2011
DOI: 10.5012/jkcs.2011.55.4.633
|View full text |Cite
|
Sign up to set email alerts
|

Iron (III) Phosphate as a Green and Reusable Catalyst Promoted Chemo Selective Acetylation of Alcohols and Phenols with Acetic Anhydride Under Solvent Free Conditions at Room Temperature

Abstract: 요 약. 알코올과 페놀 계 화합물을 아실화시키는 반응에서, iron (III) phosphate 촉매를 사용했을 때에, 좋은 수율로 아 실화 화합물을 얻었다. Iron (III) phosphate 촉매는 또한 친환경 반응에 재사용할 수 있는 친환경 촉매이다. 주제어: 아실화 반응, 알코올과 페놀, 무용매 ( Solvent free), 촉매, Iron (III) phosphateABSTRACT. Iron (III) phosphate was employed as an efficient catalyst for the chemo selective acetylation of alcohols and phenols under solvent free condition at room temperature and with high yields. Iron (III) phosphate is also a potential green catalyst due to solid intrinsically, reusable and with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…여러 가지 알코올의 선택적 산화반응성을 조사하기 위하여, DMF, acetone 용매에서, 산화제인 (C9H7NH)2Cr2O7를 이용하여 이차알코올들이 있을 때, 벤질알코올, 알릴알코올, 일차알코올류의 선택적 산화반응성을 각각 조사하였다. + 시클로헥실 메탄올), (펜에틸알코올 + 1-도데카놀)]들과 각각 0.01 mole을 실온에서 반응시켰다 [11]. 산화반응에서 생성된 알데히드와 케톤은 수율은 GC로 구하였다.…”
Section: 서론unclassified
“…여러 가지 알코올의 선택적 산화반응성을 조사하기 위하여, DMF, acetone 용매에서, 산화제인 (C9H7NH)2Cr2O7를 이용하여 이차알코올들이 있을 때, 벤질알코올, 알릴알코올, 일차알코올류의 선택적 산화반응성을 각각 조사하였다. + 시클로헥실 메탄올), (펜에틸알코올 + 1-도데카놀)]들과 각각 0.01 mole을 실온에서 반응시켰다 [11]. 산화반응에서 생성된 알데히드와 케톤은 수율은 GC로 구하였다.…”
Section: 서론unclassified
“…4 The universal method of TBAc synthesis is based on the esterification of tert-butanol (TBA) and acetic acid using zinc chloride (or N,N-dimethylformamide) as the catalyst. 5,6 In previous work, TBA was routinely used as a raw material for butyl rubber production or as a gasoline additive agent which has been added to neat fuel, gasoline, diesel, jet fuel, aviation gasoline, and heating oil as an oxygenated fuel constituent. 7 Monton et al found that tert-butanol and tertbutyl acetate exist in a low relative volatility region.…”
Section: Introductionmentioning
confidence: 99%
“…tert -Butyl acetate (TBAc) is generally used as a solvent in the production of various chemical products, such as coatings, enamels, nitrocellulose, and adhesives. , In recent years, the use of TBAc, an environmentally friendly nonhazardous solvent, in surface treatment and oil stabilization has seen a dramatic increase. , One of the advantages of TBAc is that it can reduce the photochemical reactive and VOC content of target products . The universal method of TBAc synthesis is based on the esterification of tert -butanol (TBA) and acetic acid using zinc chloride (or N , N -dimethylformamide) as the catalyst. , In previous work, TBA was routinely used as a raw material for butyl rubber production or as a gasoline additive agent which has been added to neat fuel, gasoline, diesel, jet fuel, aviation gasoline, and heating oil as an oxygenated fuel constituent . Monton et al found that tert -butanol and tert -butyl acetate exist in a low relative volatility region .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of an inorganic solid acid in organic synthesis has become more popular [8][9][10][11][12]. In addition to the cases mentioned above, FePO 4 is an inexpensive, safe and available reagent [13] that has also been employed for the selective oxidation of CH 4 to CH 3 OH [14] and benzene to phenol [15], one-pot synthesis of dihydropyrimidinones and thiones [16], one-pot three component synthesis of 2,4,5-trisubstituted imidazoles [17], synthesis of 1,2,4,5-tetraarylated imidazoles [18], acetylation of alcohols and phenols with acetic anhydride [19], synthesis of bis(indolyl)methanes [20], synthesis of 1,2-disubstituted benzimidazoles [21] and synthesis of 2-disubstituted benzimidazoles [22]. In addition, a part of our programme is aimed at developing selective and environmental friendly methodologies for the preparation of fine chemicals [17][18][19][20][21]; due to the versatile biological properties of perimidines and as a continuation of our studies on the synthesis of heterocyclic compounds, we report a clean and simple synthetic method for the preparation of perimidines using FePO 4 as an efficient catalyst, which was employed as green catalyst for the reaction between 1,8diaminonaphthalene and aromatic aldehydes at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%